1990
DOI: 10.1161/01.res.67.4.835
|View full text |Cite
|
Sign up to set email alerts
|

Potassium accumulation in the globally ischemic mammalian heart. A role for the ATP-sensitive potassium channel.

Abstract: We investigated the contribution of opening of the ATP-sensitive K+ channel to extracellular accumulation of K+ during ischemia with the use of glibenclamide, a specific blocker of this K+ channel. To characterize the electrophysiological effects of glibenclamide during metabolic inhibition (by either application of dinitrophenol or hypoxia) we performed patch-clamp studies in isolated membrane patches of guinea pig myocytes and in intact guinea pig myocytes and studied action potential parameters in isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
117
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(128 citation statements)
references
References 48 publications
11
117
0
Order By: Relevance
“…In conclusion, the stable K ϩ concentrations that we used to create a myocardial heterogeneity correspond to the levels of [K ϩ ] o detected during the first 10 min after coronary occlusion (58,61). This early period of acute ischemia is characterized by a maximum rate of incidence of ventricular arrhythmias (13,33), and the phenomenon described in this work can be one of the scenarios for reentry induction in phase 1a arrhythmias.…”
Section: Discussionsupporting
confidence: 51%
“…In conclusion, the stable K ϩ concentrations that we used to create a myocardial heterogeneity correspond to the levels of [K ϩ ] o detected during the first 10 min after coronary occlusion (58,61). This early period of acute ischemia is characterized by a maximum rate of incidence of ventricular arrhythmias (13,33), and the phenomenon described in this work can be one of the scenarios for reentry induction in phase 1a arrhythmias.…”
Section: Discussionsupporting
confidence: 51%
“…That ion is known to treble in concentration in the extracellular space during the preceding 10 min of ischaemia in the rat (Wilde et al, 1990).…”
Section: : Discussionmentioning
confidence: 99%
“…However, it has to be emphasized that these experiments were performed in the coronary circulation of animals, and with the use of high glibenclamide concentrations. Moreover, in such experiments glibenclamide has been shown to reduce basal coronary blood flow [37,42]. In contrast, our experiments were performed in the human forearm vascular bed with relatively low glibenclamide concentrations.…”
mentioning
confidence: 99%
“…Indeed, several reports have suggested that only the initial cellular potassium efflux after ischaemia is mediated by activation of K ATP channels [36,37]. The delayed vasodilator response to ischaemia seems predominantly to be mediated by other mechanisms, including the endothelial release of endothelium-derived nitric oxide [38] and prostaglandins [39,40].…”
mentioning
confidence: 99%